POTRET PERJUANGAN PEREMPUAN OLEH ISRA HADID DAN DEYA RA’AD DALAM A WOMAN IS NO MAN KARYA ETAF RUM - Mubarokati, Rihaadatul 'Aisyil (Adabiyyāt: Jurnal Bahasa dan Sastra, 2022)
A Women Is No Man presents the struggle of Isra Hadid and Deya Ra’ad to break the gender hierarchy in the family wrapped in religious dogma and try to regain their rights and freedoms as human women. Religion in this story becomes a legitimator for those main characters’ families to justify the practice of patriarchy in their traditions. Thus, the same oppression experienced by those two main female characters from different generations and growing up in different countries continues. By using the theory of Islamic feminism proposed by Wadud, the struggles experienced by Isra Hadid and Deya Ra’ad show the injustice between men’s and women’s positions in their tradition marginalizing and exploiting women, which does not exist in the understanding of Islam. This study applies the Narratology method to reveal the struggles of the two female characters by re-reading religious texts in reproducing meaning through Amina Wadud’s Islamic feminism. Islamic feminism theory is a theory that focuses on equality between men and women in Islam. Islamic feminism by Wadud tries to explain misconceptions about the status and role of women in Islam through re-reading the Qur’an and Hadith from a woman’s perspective. The results obtained from the study conclude that the inequality in the status and role of women in the Isra and Deya’s family traditions still continues to the next generation, although the intensity is reduced.